دور مستشار التوجيه في التخفيف من حدة العنف في الوسط المدرسي من وجهة نظر مستشاري التوجيه مركز التوجيه المدرسي و المهني بولاية الاغواط - عباسي فاطمة الزهراء; بوزيد عائشة; جمال الدين فطام (My University, 2019)
The present study aimed at revealing the role of the guidance counselor in alleviating the violence in the school environment. And this through the view of guidance counselors in the state of Laghouat. The study was conducted on an intentional sample of guidance counselors. The study included all the samples of guidance counselors in Laghouat which represented 33 counselors distributed among 10 males by 30,30% and 23 females by 69.69%. We have relied on the analytical descriptive approach that addressed all elements of the sample. The questionnaire was used in this study. This research has focused on four partial hypotheses within the general hypothesis: _ The first general hypothesis is correct: the guidance counselor has a role in mitigating violence in the school environment. For the second hypothesis, it is not statistically significant, and therefore there are no gender differences in the alleviation of violence in the school environment. Therefore, we accept the zero hypothesis and represent that there are no statistically significant differences between the sexes in reducing the violence in the school. For the third hypothesis: we conclude that the guidance counselor contributes significantly to the mitigation of verbal violence in the school. The fourth hypothesis: it has been proven correct. The guidance counselor contributes significantly to the alleviation of physical violence in the school environment. As for the fifth hypothesis, it was found that the guidance counselor contributes significantly to the alleviation of violence in the school environment